DEVELOPMENT OF METHODOLOGICAL TRAINING IN PROFESSIONAL EDUCATION OF FUTURE TEACHERS - Sultansaidova Mushtariy Abzalxanovna (Scholar Express Journal, 2023)
The research aims to identify the factors affecting the quality of methodological training of future preschool teachers in the modern educational environment. Moreover, to identify the factors influencing the effectiveness of methodological training of future preschool teachers in the digital environment, the method of theoretical analysis was applied.
Keywords: development; research; methodological training; future teacher